2010
DOI: 10.1002/ajmg.a.33498
|View full text |Cite
|
Sign up to set email alerts
|

A new Ehlers–Danlos syndrome with craniofacial characteristics, multiple congenital contractures, progressive joint and skin laxity, and multisystem fragility‐related manifestations

Abstract: We previously described two unrelated patients showing characteristic facial and skeletal features, overlapping with the kyphoscoliosis type Ehlers-Danlos syndrome (EDS) but without lysyl hydroxylase deficiency [Kosho et al. (2005) Am J Med Genet Part A 138A:282-287]. After observations of them over time and encounter with four additional unrelated patients, we have concluded that they represent a new clinically recognizable type of EDS with distinct craniofacial characteristics, multiple congenital contractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(130 citation statements)
references
References 15 publications
6
124
0
Order By: Relevance
“…The prominent feature of congenital foot malformations is present in all the patients they describe, delineated as clubfeet in ATCS and in its milder form as talipes equinovares. Furthermore, at least one of the symptoms of disturbed blood coagulation, delayed wound healing, ecchymoses, and hematoma formation that we described in ATCS was present in each of their patients [Dundar et al, 1997[Dundar et al, , 2001[Dundar et al, , 2009Janecke et al, 2001;Kosho et al, 2010]. Although there are minor differences in the clinical findings reported in each article dealing with CHST14 mutations, all are well within the range of expected clinical variability.…”
supporting
confidence: 62%
“…The prominent feature of congenital foot malformations is present in all the patients they describe, delineated as clubfeet in ATCS and in its milder form as talipes equinovares. Furthermore, at least one of the symptoms of disturbed blood coagulation, delayed wound healing, ecchymoses, and hematoma formation that we described in ATCS was present in each of their patients [Dundar et al, 1997[Dundar et al, , 2001[Dundar et al, , 2009Janecke et al, 2001;Kosho et al, 2010]. Although there are minor differences in the clinical findings reported in each article dealing with CHST14 mutations, all are well within the range of expected clinical variability.…”
supporting
confidence: 62%
“…Therefore, we tentatively proposed that the two patients represented a clinically recognizable subgroup of EDS type VIB [12]. Through their long-term clinical evaluation as well as four additional unrelated Japanese patients including one with parental consanguinity and another reported by Yasui et al [14], we concluded that they-four female patients and two male patients aged 4-32 years, represented a new clinically recognized type of EDS with distinct craniofacial characteristics, multiple congenital contractures, progressive joint and skin laxity, and multisystem fragility-related manifestations [15]. The disorder has been registered as EDS Kosho Type (EDSKT) in the London Dysmorphology Database (http://www.lmdatabases.com/index.html) and in POSSUM (http://www.possum.net.au/).…”
Section: Eds Kosho Typementioning
confidence: 56%
“…Sometimes what appears to be phenotypic diversity at a locus turns out, in fact, to be a single clinical entity. What was recently described as a ''new Ehlers-Danlos syndrome with craniofacial characteristics, multiple congenital contractures, progressive joint and skin laxity, and multisystem fragility-related manifestations'' [Kosho et al, 2010] was determined to have similar features to an existing entity in OMIM, adducted thumb-clubfoot syndrome (ATCS; MIM# 601776), which is due to mutations in CHST14 (MIM# 608429). Some of the patients reported by Kosho et al [2010] had been reported earlier [Kosho et al, 2005] as having Ehlers-Danlos syndrome VIb (EDS VIB).…”
Section: Nosologymentioning
confidence: 99%
“…In the original description of adducted thumb-clubfoot syndrome by Dundar et al [1997], the patients were very young, and joint contractures were the most prominent features. The patients reported by Kosho et al [2010] were older, and skin and joint laxity were the most prominent features.…”
Section: Nosologymentioning
confidence: 99%